Physical and socioeconomic burden of caregiving on family caregivers of children with cancer at a tertiary Hospital in Ghana - Beatrice A. A. Bekui; Lillian Akorfa Ohene; Caroline Badzi; Menford Owusu Ampomah; Lydia Aziato (Wiley, 2023)
Abstract Background Childhood cancer is proportionately higher in Africa and these result in increased demands on caregivers. The inability of affected children to take care of themselves; coupled with prescribed medical interventions presents physical and social burdens on family caregivers. Aims and methods This study used a qualitative exploratory design to explore the physical and socioeconomic challenges for family caregivers of children diagnosed with cancer and receiving care at one of the biggest tertiary hospitals in Ghana. A total of thirteen family caregivers of children with cancer were interviewed. Findings Two major themes were identified: Burden of care on Physical Health and Socioeconomic burdens of caregiving on the family caregiver. It was reported that family caregivers encounter physical challenges such as Aches and Pains when performing caregiving activities, Loss of Appetite, Fatigue, Compromised Functional State and Sleep Disruption. The second theme, Socioeconomic burdens of caregiving on family caregivers account for the consequences of caregiving on social lives, family relationships, finance and employment. Conclusions and recommendations The study recommends that measures that provided relief for the caregivers such as teaching them to adopt local measures of pain relief such as massage should be encouraged. Policies should adopt measures that encourage caregivers to have some days of rest whiles providing care to their children with cancer. Also, health insurance packages that provide relief for the cost of accessing healthcare, should be extended to children with cancers to support their caregivers.